Kajian Pengaruh Perbedaan Kerapatan Tanam dan Tahun Tanam terhadap Produktivitas Kelapa Sawit - Prasetio, Ryan; Wirianata, Herry; Tarmadja, Samsuri (Jurnal Agro Industri Perkebunan, 2023)
The oil palm yield depends on its genetic and the interaction with environmental factors is affected by spatial arrangement of palm trees. The research objectives are to determine the effect of population density and planting year on oil palm productivity and vegetative growth. This research uses a factorial design arranged with a randomized complete design. Secondary data are palm productivity, fresh bunch number and bunch weight that were collected for three years (2019—2022). Primary data are stem height, frond length, and stem gird which were measured on 90 trees for each treatment combination. There are nine combinations with 810 palm trees that were sampled from 27 estate blocks (30 hectares for one block). The results showed that productivity and amount of oil palm FFB at densities ≥ 142, 136-141, and ≤ 135 SPH and planting years 2007, 2009 and 2011 (mature crop 12-15, 10-13, and 8-11 years) did not show significant differences. The heavier bunch weight was produced palm tree planted in 2007 with density ± 135 trees.ha-1.